Implementation of the POE2WE (Prediction, Observation, Explanation, Elaboration, Write, and Evaluation) Learning Model to Improve Understanding of Chemical Concepts Regarding Buffer Solutions among Grade XI Students at SMAN 2 Siak Hulu - Ezra Yulyta Hasibuan; Rasmiwetti; Dedi Futra (Darul Yasin Al Sys, 2026)
Students’ limited conceptual understanding of buffer solutions presents a substantial learning challenge because the topic integrates acid–base concepts, chemical equilibrium, and pH calculations. This study examined the effectiveness of the Prediction, Observation, Explanation, Elaboration, Write, and Evaluation (POE2WE) learning model in improving Grade XI students’ conceptual understanding of buffer solutions at SMAN 2 Siak Hulu. A quasi-experimental method with a nonequivalent control-group pretest–posttest design was employed. Class XI.4 served as the experimental group, while Class XI.5 served as the control group; both classes were selected through purposive sampling. Data were collected using an essay-based conceptual-understanding test and analyzed through normality and homogeneity tests, a t test, and normalized gain analysis. The findings demonstrated a significant difference in the improvement of conceptual understanding between the two groups, with the calculated t value (2.34) exceeding the critical value (1.998) at the 5% significance level. The experimental group achieved a normalized gain of 0.72, categorized as high, whereas the control group obtained a normalized gain of 0.56, categorized as moderate. Improvements across all indicators of conceptual understanding were also greater in the experimental group. These findings demonstrate that the POE2WE learning model effectively improves students’ conceptual understanding of buffer solutions. The model therefore offers an alternative instructional approach that actively engages students in constructing, explaining, applying, and evaluating their understanding of chemistry concepts.